River water quality assessment based on a multi-descriptor approach including chemistry, diatom assemblage structure, and non-taxonomical diatom metrics. (January 2018) - Pandey, Lalit K.; Lavoie, Isabelle; Morin, Soizic; Park, Jihae; Lyu, Jie; Choi, Soyeon; Lee, Hojun; Han, T.
Graphical abstract: Highlights: Impacted sites showed a dominance of small-sized diatoms, while larger-sized diatoms prevailed in less-impacted sites. Impacted sites showed higher proportion of unhealthy/dead frustules, lower cell count, as well as lower diversity and species richness. Higher incidence of lipid bodies and valve deformities were observed at impacted sites, compared to less-impacted sites. Abstract: In the present study, the ecological status of four major South Korean rivers flowing near industrial complexes is assessed using physico-chemical analyses and various descriptors based on benthic diatom assemblages. Principal component analysis conducted with physical and chemical variables singled-out four sites as more severely impacted (higher concentration of metals and total nitrogen, higher conductivity and biological oxygen demand), while the remaining 12 sites indicated less impacted conditions, although showing nutrient enrichment. Less-contaminated sites based on physico-chemical properties showed higher cell densities, higher richness and diversity, a larger proportion of live and healthy-looking diatoms, lower production of lipid bodies (in terms of number and size) and fewer teratologies than more-contaminated sites. Non-taxonomical metrics (cell heath status, cell size, lipid bodies and valve deformities) were in good agreement with traditional taxonomical metrics (assemblage structure, richness, diversity). Overall, water quality assessment based on diatom assemblages and diatom-based metrics had a good fit with the available physico-chemical data and agreed on the most impacted sites. However, additional sites showed signs of degradation based on the diatom metrics used. This suggests that the use of biotic indicators provides useful complementary information on the health status at the selected sites.